Re-examining Firm Size and Corporate Social Responsibility: The Visibility Approach - Golrida Karyawati P; Mira Muliani; Prem Lal Joshi (Emerging Markets Journal, 2019)
In a previous study on the firm size and corporate social responsibility (CSR) participation conducted by Golrida, et al (2017), different result is reported with Udayasankar’s hypothesis (2008) which states a U-shape relationship of firm size and CSR participation.  However, it is arqued that Udayasankar hyppothesis is better applicable in developed countries, while in developing countries an inverted - U shape relationship is found. But, Golrida et al (2017) can only prove the form of relationship using two perspectives stated by Udayasankar, which are operating scale and resourcess access.  The proxy of visibility could not capture the inverted U shape relationship due to measurement problem in the previous study. This study aims at re-examining the relationship between firm size and CSR participation from the visibility perpective by employing two proxies of visibility, which are analyst coverage and news coverage respectively.  Indonesian companies are chosen to capture the context of developing country. Content analysis is done in obtaining CSR data of 433 companies listed on Indonesian Stock Exchange on 2012, while the data of visibility proxies are  extracted from Thomson Reuters and selected news portal namely, Detik.com. The result of study shows that both visibility proxies, which are Analysts Coverage and Media Coverage form inverted U- shape relationship with CSR participation. The findings in this study contribute to the literature that, the form of firm size and CSR participation relationship in the context of developing countries is different than those in developed countries.